Strategic human resource management and performance in public hospitals in Ethiopia - Gile, Philipos Petros; van de Klundert, Joris; Buljac-Samardzic, Martina (Frontiers in Public Health, 2022)
Strategic Human Resource Management and Performance in Public Hospitals in Ethiopia Abstract Background: Ethiopian public hospitals struggle to meet health care needs of the Ethiopian population, in part because of the persistent human resources crisis. The health reforms and tight human resource management (HRM) regulation of the government have resulted in limited progress towards addressing this crisis. This study aims to analyze how the strategic HRM practices adopted by Ethiopian public hospitals influence employee outcomes, organizational outcomes, and patient outcomes. Methods: Structured interviews were conducted with 19 CEOs and HR managers from 15 hospitals. Four focus groups were also conducted, with 38 participants (professionals and line managers). The transcripts were thematically analyzed using ATLAS.ti 8. Deductive coding was used based on the Contextual SHRM framework, while remaining open for codes that emerged. Results: Intended HR practices are influenced by mandatory strict government regulations. Nevertheless, some room for self-selected (bundles of) HR practices is perceived by hospitals. Employees perceive that governmental steered HR practices may not match its intentions due to implementation issues, related to lack of support and skilled management and HR professionals. These problems are leading to dissatisfaction, demotivation, moonlighting and turnover of skilled professionals and perceived to consequently negatively influence performance (i.e. patient satisfaction and waiting time). Conclusions: To motivate and retain health care professionals and consequently improve outcomes for patients, leaders in hospitals need autonomy to develop tailor made SHRM systems. Due to a lack of perceived leeway and management skills, the higher management in Ethiopian public hospitals , however, hardly succeeds at developing tailored SHRM systems. Our results suggest that loosening the tight regulation and increasing hospital budgets for SHRM may partially remedy the persistent problems.